Phylogenomic Classification and the Evolution of Clonal Complex 5 Methicillin-Resistant Staphylococcus aureus in the Western Hemisphere - Challagundla, Lavanya; Reyes, Jinnethe; Rafiqullah, Iftekhar; Sordelli, Daniel O.; Echaniz-Aviles, Gabriela; Velazquez-Meza, Maria E.; Castillo-Ramírez, Santiago; Fittipaldi, Nahuel; Feldgarden, Michael; Chapman, Sinéad B.; Calderwood, Michael S.; Carvajal, Lina P.; et al. (Frontiers in Microbiology, 2018)
Clonal complex 5 methicillin-resistant Staphylococcus aureus (CC5-MRSA) includes multiple prevalent clones that cause hospital-associated infections in the Western Hemisphere. Here, we present a phylogenomic study of these MRSA to reveal their phylogeny, spatial and temporal population structure, and the evolution of selected traits. We studied 598 genome sequences, including 409 newly generated sequences, from 11 countries in Central, North, and South America, and references from Asia and Europe. An early-branching CC5-Basal clade is well-dispersed geographically, is methicillin-susceptible and MRSA predominantly of ST5-IV such as the USA800 clone, and includes separate subclades for avian and porcine strains. In the early 1970s and early 1960s, respectively, two clades appeared that subsequently underwent major expansions in the Western Hemisphere: a CC5-I clade in South America, and a CC5-II clade largely in Central and North America. The CC5-I clade includes the ST5-I Chilean/Cordobes clone, and the ST228-I South German clone as an early offshoot, but is distinct from other ST5-I clones from Europe that nest within CC5-Basal. The CC5-II clade includes divergent strains of the ST5-II USA100 clone, various other clones, and most known vancomycin-resistant strains of S. aureus, but is distinct from ST5-II strain N315 from Japan that nests within CC5-Basal. The recombination rate of CC5 was much lower than has been reported for other S. aureus genetic backgrounds, which indicates that recurrence of vancomycin resistance in CC5 is not likely due to an enhanced promiscuity. An increased number of antibiotic resistances and decreased number of toxins with distance from the CC5 tree root was observed. Of note, the expansions of the CC5-I and CC5-II clades in the Western Hemisphere were preceded by convergent gains of resistance to fluoroquinolone, macrolide and lincosamide antibiotics, and convergent losses of the staphylococcal enterotoxin p (sep) gene from the immune evasion gene cluster of phage Sa3. Unique losses of surface proteins were also noted for these two clades. In summary, our study has determined the relationships of different clades and clones of CC5 and has revealed genomic changes for increased antibiotic resistance and decreased virulence associated with the expansions of these MRSA in the Western Hemisphere.